The value of price - and quantity-fixing contracts of piglets in Finland - Pietola, Kyösti S.; Wang, H. Holly (Oxford, 2000)
This paper estimate the value for price- and quantity-fixing contracts to trade weaned piglets from farrowing farms to finishing farms. These values are estimated using quasi option values, driven up by volantile returns to investment in hog production units. The results suggest that hog producers haven an incentive to choose vertically coordinated or integrated production systems when investing in hog production. The value of the price- and quantity-fixing contract was estimated as 7.3 pre cent of investment outlay in farrowing units and 2.7 per cent of investment outlay in finishing units. The corresponding value of the option to suspend production in finishing units was estimated at 1.7 per cent.
Keywords: Ma